A re-evaluation of the basal age in the DSDP hole at Site 534, Central Atlantic. (December 2017) - Brikiatis, Leonidas
Highlights: Re -dating the basal ages of the DSDP Site 534A and ODP Site 801C. Demonstrating a common pattern in the Middle Oxfordian δ¹³Ccarb variation. Fine dating the opening of the Hispanic corridor. Abstract: For 30 years, the initial sedimentation following the opening of the western Central Atlantic has been considered to be of Middle Callovian age (approximately 164.5 Ma) based on the biochronostratigraphical estimation for the basal sedimentary unit of the borehole from Site 534A of the Deep Sea Drilling Program (DSDP). That age has been used in kinematic models of the opening of the Central Atlantic. A reconsideration of the available biochronostratigraphical data and correlation of the δ¹³Ccarb record from Site 534A with those from the Tethyan and North Atlantic records suggest that the initial sedimentation at Site 534A is, in fact, of Middle Oxfordian age (approximately 160.6 Ma). The high biostratigraphic similarity among the basal sedimentary units of the boreholes at DSDP Site 534A and Ocean Drilling Program Site 801C in the Western Pacific suggest the same age for both sites. The Middle Oxfordian δ¹³Ccarb records from the different sites covary, marking the same palaeoenvironmental changes, although such an agreement was not previously acknowledged. A combination with additional data proposes that Middle Oxfordian age corresponds to the precise date of the opening of the Hispanic Corridor between the Atlantic and Pacific oceans. Graphical abstract: